Untargeted Metabolomics Studies of H9c2 Cardiac Cells Submitted to Oxidative Stress, β-Adrenergic Stimulation and Doxorubicin Treatment: Investigation of Cardiac Biomarkers - Lima, Monica Força; Amaral, Alan Gonçalves; Moretto, Isabela Aparecida; Paiva-Silva, Franckson Jhonne Torres Neves; Pereira, Flávia Oliveira Borges; Barbas, Coral; dos Santos, Aline Mara; Simionato, Ana Valéria Colnaghi; Rupérez, Francisco Javier (Frontiers in Molecular Biosciences, 2022)
One of the biggest challenges in the search for more effective treatments for diseases is understanding their etiology. Diseases such as cardiovascular diseases are a great example of this, given the high number of deaths annually. One of the factors responsible for its occurrence and that needs investigation is oxidative stress, which occurs when there is an imbalance between oxidant and antioxidant species in the body. Excess reactive oxygen species (ROS) are primarily responsible for this condition, and clinical and scientific reports have presented data reporting a significant increase in ROS when therapeutic drugs, such as doxorubicin and isoproterenol, are administered. In this context, the aim of this study was to search for potential biomarkers that could be associated with oxidative stress in cardiomyocytes. For this purpose, the differentiated heart cells of the H9c2 lineage (that present characteristics very similar to myocytes obtained from rat heart) were submitted to oxidative stress conditions by treatment with doxorubicin (DOX), isoproterenol (ISO) and hydrogen peroxide (PER). The cell extract and the supernatant obtained from the culture medium were then evaluated by CE-ESI(+)-TOF-MS. Following signal processing, statistical analyses and feature annotations, the results indicate changes in the aspartate, serine, pantothenic acid, glycerophosphocholine, glutathione metabolism, among others in the cell extract.